2020
DOI: 10.1177/0308518x20931105
|View full text |Cite
|
Sign up to set email alerts
|

Who is contributing? Scientific collaborations on COVID-19

Abstract: The new coronavirus makes the world recognize that all nations share the same future in the era of globalization. Global cooperation, especially scientific collaboration, is the key to accelerate understanding of the COVID-19 virus and the fight against the pandemic. By visualizing the research cooperation network on COVID-19 as of April 15, 2020, we found that cities and institutes in China played an important role in promoting COVID-19 research cooperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Most countries/regions regard the US as the strongest scientific partner. Thirdly, China has played a vital role in the scientific research and cooperation on COVID‐19, which is not only reflected in the number of published papers (Duan et al ., 2020) but also in its extensive international cooperation (Mo & Zhou, 2020; Wu et al ., 2020; Zhou et al ., 2020). Fourth, China and the US were the closest partners in the current international scientific cooperation of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most countries/regions regard the US as the strongest scientific partner. Thirdly, China has played a vital role in the scientific research and cooperation on COVID‐19, which is not only reflected in the number of published papers (Duan et al ., 2020) but also in its extensive international cooperation (Mo & Zhou, 2020; Wu et al ., 2020; Zhou et al ., 2020). Fourth, China and the US were the closest partners in the current international scientific cooperation of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…It took only 6 months from the discovery of the Novel Coronavirus (COVID‐19) to more than 6 million confirmed cases and 300,000 deaths, which not only proves that the COVID‐19 is too contagious to be overcome but also demonstrates the common destiny of all countries and regions in the era of globalization (Nature Editorial, 2020c; Washington, 2020). In fact, when this outbreak was declared as a Public Health Emergency of International Concern (PHEIC) on 30 January 2020 by the WHO, it was already indicated that international cooperation is the key to combating this pandemic (Berkley, 2020; Duan et al ., 2020; Nature Editorial, 2020a, 2020b; Nature Medicine Editorial, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the data gathered on 15 April 2020, 1,265 article reviews and letters were jointly published by 1,608 institutions in 752 cities from 84 countries. When it comes to cooperation, 77 countries (regions) have cooperated internationally 1,180 times, 354 cities have cooperated 2,052 times, and 1,495 institutes have conducted 7,192 institutional collaborations (Duan et al 2020). Another example of cooperation at the state level is where several countries have sent medical equipment to Indonesia.…”
Section: Global Solidarity and Cooperationmentioning
confidence: 99%
“…Previous studies have explored how to prevent and control the spread of the epidemic from multiple perspectives, including public health management (8), clinical features and pathological mechanism research (9,10), vaccines and diagnostic methods (11,12), transmission models (13), the auxiliary application of information technology (14) and international cooperation (15). With respect to research literatures on international cooperation, many literatures emphasized that scientific collaboration in the field of health plays an important role in reducing the infection rate and mortality of infectious diseases (16)(17)(18)(19)(20). In addition, some literatures analyzed the prevention and control of infectious diseases from the perspective of the construction of global health governance mechanisms (21,22).…”
Section: Introductionmentioning
confidence: 99%